Anti-influenza properties of tiliroside isolated from Hibiscus mutabilis L. (1st March 2023) - Xiao, Mengjie; Zhang, Tianbo; Cao, Fei; Liang, Weihong; Yang, Yinhua; Huang, Tao; Tang, Yun-Sang; Liu, Bo; Zhao, Xin; Shaw, Pang-Chui
Abstract: Ethnopharmacological relevance: Fu Rong Ye (FRY), the leaf of Hibiscus mutabilis L., is a Chinese medicinal herb used to treat coughs and respiratory diseases. FRY is the major herbal component of the patent medicine Fupo Ganmao Granules for treating common cold. However, its anti-influenza active components and mechanism were not identified. Aim: Here, we aim to a) isolate the anti-influenza phytochemicals from FRY extract and b) explore its anti-flu mechanism. Material and methods: Bioassay guided isolation was performed to get anti-influenza virus components. Influenza virus infected cells and mouse model were employed for efficacy evaluation. Results: Using bioassay-guided isolation, the flavonoid tiliroside was obtained, which inhibited four IAV strains in MDCK cells with EC50 ranging from 3.87 to 27.61 μM by suppressing the viral ribonucleoprotein activity. Tiliroside also significantly downregulated the expression of cytokines/chemokines in A549 cells, and protected 50% of PR8-infected BALB/c mice from death and at 800 mg/kg/day, improved lung edema conditions. Conclusion: Tiliroside is effective for influenza virus infection treatment and promising for further drug development. This study is the first to demonstrate that tiliroside in FRY acts against influenza virus. Graphical abstract: Image 1 Highlights: Tiliroside was isolated from leaves of Hibiscus mutabilis L.. Tiliroside inhibited ribonucleoprotein (RNP) activity. Tiliroside exhibited antiviral activities in mice. This study supports the clinical application of FRY in influenza treatment.